The Slow Living Lifestyle as an Instrument of Maqāṣid al-Sharī‘ah in Maintaining Muslim Family Resilience - Savvy Dian Faizzati (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
This study aims to analyze the relationship between the principles of slow living and maqāṣid al-syarī‘ah in maintaining the resilience of Muslim families. Amid the acceleration of modern life, which often triggers domestic tension, the concept of slow living offers a spiritual and social paradigm oriented toward balance, simplicity, and mindfulness. This research employs a normative legal method with conceptual and philosophical approaches. The primary data sources include the Qur’an, Hadith, the Compilation of Islamic Law (KHI), as well as classical and contemporary Islamic legal literature. The analysis is conducted descriptively and analytically by interpreting the values of maqāṣid al-syarī‘ah particularly hifẓ al-nafs (protection of life), hifẓ al-‘aql (protection of intellect), and hifẓ al-nasl (protection of lineage) as theological and ethical foundations for implementing slow living. The findings indicate that the principles of slow living are not in conflict with Islamic law; rather, they represent an actualization of spiritual values such as zuhd (asceticism), qana‘ah (contentment), and tawāzun (balance) in family life. In conclusion, the integration of a slow living lifestyle can serve as a normative strategy for strengthening the resilience of Muslim families in the digital era.